Effects of acupuncture combined with strength training and whole-body vibration training on patients with chronic ankle instability: a randomised controlled trial - He, Jian; Chang, Shuwan; Liu, Heng (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aims to investigate the rehabilitative effects of adding whole-body vibration training (WBVT) on the ankle function, muscle strength, and balance ability of patients with chronic ankle instability (CAI) based on strength training combined with acupuncture.MethodsA total of 49 university students with unilateral CAI was divided into an experimental group (strength training + acupuncture + WBVT, n = 25) and a control group (strength training + acupuncture, n = 24). The intervention lasted for 8 weeks (3 times per week). The evaluation indicators included cumberland ankle instability tool (CAIT), foot and ankle ability measure (FAAM), isokinetic muscle strength, proprioception, and balance ability.Results1) At the 8th week, intergroup comparison showed that the experimental group had higher FAAM-ADL (p = 0.043) and peak plantar flexion torque of the ankle (p = 0.020) than the control group. The anterior-posterior displacement (p = 0.002) and average speed (p = 0.046) were lower than those in the control group. 2) At the 8th week compared with baseline, within-group comparison showed that in the experimental group, CAIT, FAAM-ADL, and FAAM-Sport increased by 16.2, 36.2, and 37.8% respectively (p < 0.01). The peak torque of ankle dorsiflexion, plantar flexion, inversion, and eversion increased by 34.2, 19.4, 12.3, and 12.3% respectively (p < 0.05). The threshold of motion perception of ankle plantar flexion decreased by 15.1%. The anterior-posterior and medial-lateral displacements decreased by 22.2% and 17.5% respectively, and the average speed decreased by 31.2% and 13.8% respectively (p < 0.05). In the control group, FAAM-ADL and FAAM-Sport increased by 20.9% and 26.3% respectively (p < 0.01). The anterior-posterior and medial-lateral displacements decreased by 10.9% and 12.5% respectively, and the average speed decreased by 18.9% and 9.2% respectively (p < 0.05).ConclusionAdding WBVT to strength training and acupuncture significantly improves ankle function, plantar flexion strength, and anterior-posterior balance in CAI patients, supporting its integration into comprehensive, non-surgical rehabilitation protocols.